Zróżnicowanie wybranych cech wegetatywnego potomstwa starych drzew sosny zwyczajnej Pinus sylvestris L. z Puszczy Augustowskiej - Matras-Zarzecka, Małgorzata; Zarzecki, Artur (Leśne Prace Badawcze, 2019)
This study was carried out in the clone archive of old Scots pine Pinus sylvestris L. trees located in the Augustowska Primeval Forest. The aim of the study was to determine the intra-clonal diversity among quantitative and qualitative traits of the vegetative progeny of Scots pine trees older than 200 years. Our analyses included traits such as survival rate, height and diameter at breast height (DBH), stem straightness, length and width of the crowns as well as branch thickness and growth angle. There was no significant correlation between the age of mother trees and the traits of their vegetative progeny. However, mother trees did affect the survival of the progeny. In overall, the survival rate of grafts in the archive is high (about 80% at the age of 13) and there have been no significant fluctuations in recent years. Nevertheless, the variability of quantitative traits among vegetative progeny was high with the average height ranging from 2.16 m up to 6.71 m, and in the case of DBH ranging from 3.23 cm to 12.1 cm. Both, height of trees and their DBH, were significantly different among the analyzed clones. These intra-clone differences in growth traits indicate a high environmental impact on the growth and performance of clones. However, the diversity of quantitative and qualitative traits is comparable to the differences observed in economic seed orchards with seedlings at a similar age.Most of the genotypes planted in the archive are fully viable and have matured to the stage of seed production. The clone archive can thus be viewed as both, a conservation effort and to obtain valuable seeds from the point of view of tree breeding. Therefore, establishing archives of tree clones using valuable genotypes is an effective method of conserving individual genotypes even of very old individuals.